2013
DOI: 10.1115/1.4023522
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Interaction Between a Platelet and an Erythrocyte: Effect of Erythrocyte Deformability, Dynamics, and Wall Proximity

Abstract: We present three-dimensional numerical simulations of hydrodynamic interaction between a red blood cell (RBC) and a platelet in a wall-bounded shear flow. The dynamics and large deformation of the RBC are fully resolved in the simulations using a fronttracking method. The objective is to quantify the influence of tank treading and tumbling dynamics of the RBC, and the presence of a bounding wall on the deflection of platelet trajectories. We observe two types of interaction: A crossing event in which the plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…4b ), demonstrating a critical role for RBCs in promoting the diabetic hyperadhesive phenotype. RBCs have a well-defined role in enhancing platelet transport to the vessel wall (margination) 42 , 43 and recent rheological and modeling studies demonstrated that RBCs push and subject platelets to collision forces (compression) 44 , 45 , although how compression forces influence platelet adhesive function remains largely unknown. To address this, we developed a novel compression assay using a biomembrane force probe (BFP).…”
Section: Resultsmentioning
confidence: 99%
“…4b ), demonstrating a critical role for RBCs in promoting the diabetic hyperadhesive phenotype. RBCs have a well-defined role in enhancing platelet transport to the vessel wall (margination) 42 , 43 and recent rheological and modeling studies demonstrated that RBCs push and subject platelets to collision forces (compression) 44 , 45 , although how compression forces influence platelet adhesive function remains largely unknown. To address this, we developed a novel compression assay using a biomembrane force probe (BFP).…”
Section: Resultsmentioning
confidence: 99%
“…4,7275 Modeling blood as a continuum fluid is far more computationally efficient for calculation of complex velocity fields in vessels and does not require detailed descriptions of single cell dynamics. For simulations of thrombosis that involve single platelets depositing to a growing thrombus under flow conditions, the blood is still often treated as a continuum fluid, however the near wall excess concentration of platelets must be calculated or imposed as a way of accounting for the suspension nature of flowing blood.…”
Section: Introductionmentioning
confidence: 99%
“…In looking to explain the relationship between RBC hematocrit and bleeding, previous researchers have established that the distribution of platelets in arteries and arterioles (and microchannels of similar dimensions) is not uniform-platelets predominantly reside near the channel walls while RBCs occupy most of the volume close to the center in vitro (3)(4)(5)(6)(7), in silico (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and in vivo (18,19).…”
Section: Introductionmentioning
confidence: 99%